THE EFFECT OF ZnO ADDITIVE ON PHYSICAL PROPERTIES AND MICROSTRUCTURE OF BaFe12O19 MAGNETIC MATERIAL - Sebayang, Perdamean; Sudiro, Toto; Aryanto, Didik; Nugraha, Endra (Teknologi Indonesia, 2016)
Preparation of BaFe 12 O 19 powder containing varying amount of ZnO as 5, 10, 15 and 20 % by mass were prepared by a high energy milling (HEM) for 1 hour and compacted into a pellet using 80 kgf/cm 2 in compressive pressure. The samples were sintered at elevated temperatures of 800 and 1,000 o C for 2 hours, separately. The characterization results indicated that BaFe 12 O 19 -10 mass % ZnO exhibits excellent in physical and magnetic properties that can be potentially used for recording media and microwave absorbing material applications.